Strategi Pengelolaan Sampah di Kawasan Wisata Ancol dalam Mendukung Pariwisata Berkelanjutan - Kevin Kevin; Wiwik Nirmala Sari (Lembaga Pengembangan Kinerja Dosen, 2026)
The dense tourism activities in urban coastal areas such as Taman Impian Jaya Ancol create complex ecological consequences, particularly in waste management, which directly affects environmental quality and the image of the tourism destination. The cleanliness issue in this area not only impacts aesthetic aspects but also reflects the effectiveness of destination governance. Tourism sustainability is difficult to achieve if waste management systems fail to adapt to the dynamic behavior of visitors and increasing environmental pressures. This condition raises a fundamental question regarding what kind of waste management strategy can be effectively implemented to support sustainable tourism in the Ancol tourism area, and how policies, infrastructure, and community participation contribute to this effort. This study aims to analyze waste management strategies in the Ancol Tourism Area within the context of sustainable tourism development. The research employs a qualitative descriptive approach using the Systematic Literature Review (SLR) method based on thirty journals related to waste management practices in coastal tourism areas. The analysis was conducted through identification, selection, and synthesis of data to understand management patterns and implementation challenges. The findings show that successful waste management is influenced by infrastructure availability, community participation, regulatory consistency, and adaptive technological innovation. The recommended strategies include a dynamic-load cleaning management system, community-based monitoring system, mini waste stations, circular economy principles, and cross-sector collaborative governance. These findings emphasize the importance of integrating technical and social strategies to strengthen waste management systems and promote coastal destination sustainability.